1989
DOI: 10.1111/j.1365-2141.1989.tb00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell aggregation and sedimentation: the role of the cell shape

Abstract: The influence of erythrocyte shape changes on the sedimentation rate was studied in vitro and in vivo. In vitro the highest sedimentation rate was observed with a slight degree of stomatocytosis (morphological index-0.3; i.e. one red cell out of three being a stomatocyte I). With increasing degrees of stomatocytosis the sedimentation rate gradually decreased. Echinocytosis reduced the aggregation and sedimentation very drastically; the sedimentation rate was virtually zero when echinocytosis I or higher degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 19 publications
6
34
2
Order By: Relevance
“…This is opposite to what might be expected from the fact that echinocytes undergo much less aggregation, 48, 49 but echinocytes have been shown to increase low shear viscosity irrespective of RBC aggregation. 18, 50 Washing stored RBCs had no beneficial effect at high shear rates and slightly decreased the viscosities at low shear rates.…”
Section: Discussioncontrasting
confidence: 63%
“…This is opposite to what might be expected from the fact that echinocytes undergo much less aggregation, 48, 49 but echinocytes have been shown to increase low shear viscosity irrespective of RBC aggregation. 18, 50 Washing stored RBCs had no beneficial effect at high shear rates and slightly decreased the viscosities at low shear rates.…”
Section: Discussioncontrasting
confidence: 63%
“…CRP is produced in the liver in response to IL-6 [38], whereas ESR is a laboratory phenomenon affected by fibrinogen, immunoglobulin levels and red blood cell count and shape, among other factors [39,40]. Several studies have found that pioglitazone decreased CRP concentrations [19-21], but ESR has not been measured routinely in most clinical trials of pioglitazone or other thiazolidinediones.…”
Section: Discussionmentioning
confidence: 99%
“…Reinhart et al [9,10] demonstrated that echinocytosis, induced by sodium salicylate and cytostatic mesna, led to …”
Section: Y a Sheremet'ev Et Al 214mentioning
confidence: 99%
“…Also, in the alteration of RBC aggregation for blood containing the anticoagulant CPDA1 stored at 4˚C, the effect of the plasma factor was slightly stronger than that of the cellular factor [8]. It was shown that the shape plays a crucial role in the aggregation and sedimentation of red cells [9,10].…”
Section: Introductionmentioning
confidence: 99%